THE SPECTACLE OF SPECTACLES - Appignani, Timothy; Jones, Steve; Guzman, Andrea; Archer, Jason; Neill Hoch, Indira (AoIR Selected Papers of Internet Research, 2015)
The origins of this research project are somewhat opportunistic. Given the chance, and wherewithal, in late 2013 to purchase Google Glass, Professor Steve Jones gauged interest among graduate students in our department in studying the consequences for interaction posed by Glass wearers. But like so many projects that begin simply, this one too became complicated, on several levels. In this presentation we wish to highlight the theoretical foundations on which the project rests and the possibilities for theoretical advancement that it provides. Wearable technologies such as fitness trackers, lifeloggers and even smartphones are rapidly becoming ubiquitous. Our initial questions focused at the level of interpersonal communication. It is known from studies of mobile phone use (Beranuy, et al, 2009; Licoppe and Heurtin, 2001, among others) that the inclusion of a communication device in a conversation or other interpersonal communication setting alters the setting and context for the communication. Few devices combine the modes of communication found in Google Glass (voice, image, screen, etc.). The goal of our research became to examine whether Glass may occasion similar or different disruptions or be perceived as providing new opportunities for interpersonal interaction. We were also interested in the ways Glass was being marketed, in its implications for gender and race, in its design, and in its place in the context of technologies for vision. In the five papers making up this panel we consider Google Glass from varying perspectives. We do this largely by drawing on our shared experience conducting interviews with a random sample of people from around the country on their perceptions of Glass as a recording technology, a fashion accessory, a social media device, and a new element in the interpersonal social dynamics of modern public life. The findings of these interviews suggest that contrary to its stated affordances, Glass does not provide a less conspicuous tether to the virtual world (Turkle, 2012), nor does it allow greater engagement with the social environment. Instead, our respondents read the presence of glass in social spaces as intrusive and potentially threatening. This was in one part because of the specific layering of technology across the face, which alludes to the phenomena of ocularcentrism that has become the hallmark of new digital technologies (Kenyon & Leigh, 2011). Another common threat raised was the novel way that Glass affords its users to distance them from lived experience and social engagement. To supplement these interviews some members of our panel evaluated Glass as an artifact by considering how its inchoate social significance imbues it with the “interpreative flexibility” ascribed to high quality research subjects (Pinch & Bijker, 2012, p. 23), and how the paratexts associated with Glass, including its packaging, suggest a deliberate gender conditioning of Glass consumers (Consalvo, 2007). All of the research we present centers on what wearable technologies, like Glass, suggest about the direction of our culture. In presenting our unique perspectives on this topic we deepen the scope of theoretical understanding about the augmented reality that has so changed interpersonal relations in western society (Jurgenson, 2012).